2019
DOI: 10.1038/s41598-018-37664-7
|View full text |Cite
|
Sign up to set email alerts
|

Cadaverine, a metabolite of the microbiome, reduces breast cancer aggressiveness through trace amino acid receptors

Abstract: Recent studies showed that changes to the gut microbiome alters the microbiome-derived metabolome, potentially promoting carcinogenesis in organs that are distal to the gut. In this study, we assessed the relationship between breast cancer and cadaverine biosynthesis. Cadaverine treatment of Balb/c female mice (500 nmol/kg p.o. q.d.) grafted with 4T1 breast cancer cells ameliorated the disease (lower mass and infiltration of the primary tumor, fewer metastases, and lower grade tumors). Cadaverine treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
202
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(226 citation statements)
references
References 60 publications
5
202
2
1
Order By: Relevance
“…Administration of cadaverine to mice harbouring 4T1 BrCa tumours resulted in improved outcomes (smaller tumours, fewer metastases). Furthermore, cadaverine production was shown to be decreased in BrCa patients and correlated with survival [38]. To test this in our BrCa models we used fecal metabolomic analysis by NMR and observed significant metabolic dysregulation in the microbiota of VNMA treated animals ( Figure 4).…”
Section: Discussionmentioning
confidence: 91%
“…Administration of cadaverine to mice harbouring 4T1 BrCa tumours resulted in improved outcomes (smaller tumours, fewer metastases). Furthermore, cadaverine production was shown to be decreased in BrCa patients and correlated with survival [38]. To test this in our BrCa models we used fecal metabolomic analysis by NMR and observed significant metabolic dysregulation in the microbiota of VNMA treated animals ( Figure 4).…”
Section: Discussionmentioning
confidence: 91%
“…Some evidence shows that the microbiome metabolite influences the occurrence of BC; this hypothesis may help estimate the cancer risk and prevention. For instance, cadaverine as a biogenic amine is formed through the direct decarboxylation of L-lysine (45). It is reported that cadaverine biosynthesis is reduced in the gut in early-stage BC, resulting in lower production of an anti-cancer bacterial metabolite and reduced BC invasion (45).…”
Section: Host-gut Microbiome Interactionmentioning
confidence: 99%
“…For instance, cadaverine as a biogenic amine is formed through the direct decarboxylation of L-lysine (45). It is reported that cadaverine biosynthesis is reduced in the gut in early-stage BC, resulting in lower production of an anti-cancer bacterial metabolite and reduced BC invasion (45). It is shown that bacterial metabolites can stimulate oxidative and nitrosative stress that inhibit BC progression.…”
Section: Host-gut Microbiome Interactionmentioning
confidence: 99%
“…One of the best-characterized examples is microbiome-derived cadaverine, which ameliorates breast cancer by suppressing the proliferation, metastases, and aggressiveness of tumor cells, as well as epithelial-to-mesenchymal transition (EMT). 421 Cadaverine also initiates the metabolism of tumor cells that have shifted towards glycolysis by decreasing cellular oxygen consumption. 421 Additionally, microbial-derived LCA is significantly diminished 422 and is negatively correlated with the Ki-67 index in breast cancer.…”
Section: Figmentioning
confidence: 99%